Large-Scale Crop Production for the Moon and Mars: Current Gaps and Future Perspectives - Poulet, Lucie; Engeling, Kenneth; Hatch, Tyler; Stahl-Rommel, Sarah; Velez Justiniano, Yo-Ann; Castro-Wallace, Sarah; Bunchek, Jess; Monje, Oscar; Hummerick, Mary; Khodadad, Christina L. M.; Spencer, LaShelle E.; Pechous, Josie; et al. (Frontiers in Astronomy and Space Sciences, 2022)
In this perspectives paper, we identify major challenges for space crop production: altered convection in the microgravity environment, scheduling and logistics, crew time and the need for advanced automation, robotics, modeling, and machine learning. We provide an overview of the existing space crop production gaps identified by the Kennedy Space Center (KSC) space crop production team and discuss efforts in current development in NASA projects to address these gaps. We note that this list may not be exhaustive but aims to present the baseline needs for space crop production implementation and a subset of current solutions to the greater scientific community in order to foster further ingenuity.